Fatherless dan Kekerasan Seksual - Widyastuti; Nurul Mutmainna; Novriana Ramadhana; Zulfadli Amir (Journal Psikologi Forensik Indonesia, 2023)
Sexual violence is an act involving sexual contact. Sexual violence against children is a criminal act that often occurs around us. In the city of Makassar, data showed that around 2023, cases of violence were dominated by cases of sexual violence, primarily against children. One of the forms of sexual crime that occurs is sexual harassment or rape among teenagers. Ironically, it happens repeatedly with no denial or opposition to the perpetrator, where the victim trusts the perpetrator easily. This study aims to find out the reason why sexual intercourse by the same person can happen repeatedly. In this study, the case occurred in the city of Makassar, where the informant was a victim of sexual violence committed by a friend she had not long known. Data analysis is carried out with descriptive analysis, with sources of information obtained through interviews and observations. Studies have shown that children who are close and trustworthy to other people or strangers tend never to experience intimacy and never feel safe with the important people in their lives. The absence of a father in a child's life can make the child easily trusting and close to other people because the child is looking for a replacement for that figure.